The response to dietary threonine in laying-type pullets during growth - Bonato, Melina Aparecida [UNESP]; Sakomura, Nilva Kazue [UNESP]; Gous, Robert Mervin; Dourado, Leilane Rocha Barros; Rafael, Jaqueline Moreira [UNESP]; Fernandes, João Batista Kochenborger [UNESP] (Taylor &francis Ltd, 2015)
This study aimed to provide information on the response of laying-type pullets to dietary threonine (THR) during three periods of growth prior to the onset of lay. Different batches of Dekalb White pullets were used in three separate trial periods (from 4 to 6, 8 to 11 and 13 to 16 weeks of age) using 8 dietary THR concentrations in each period, using a completely randomised design, and with each treatment being replicated 6 times, using 15 birds per replication in period 1 and 8 birds in periods 2 and 3. In period 1 the THR content (THRc) ranged from 2.3 to 7.6mg/g, in period 2 from 1.7 to 5.5mg/g, and in period 3 from 1.4 to 4.7mg THR/g feed. Body weight gain, food intake and the deposition of protein and lipid in the feather-free body and in the feathers were measured in each period. Linear regressions were fitted to all data falling below the break point defined by the broken stick regression, to estimate the efficiency of utilisation of THR. The maximum protein growth rate was 4.0 +/- 0.2, 5.3 +/- 0.4 and 3.5 +/- 0.5g/d in periods 1, 2 and 3, respectively. The efficiency of utilisation of dietary THR for THR deposition in each period was the same, at 0.85 +/- 0.1mg/mg. As dietary THRc decreased, the amount of body lipid deposition increased.4. With this information, it is possible to determine the daily requirement for THR for the potential growth of body and feather protein in growing pullets.